Dampak Pandemi Covid-19 terhadap Jumlah Wisatawan Mancanegara serta Perusahaan Mikro dan Kecil - Luh Asri Martani (CV. Syntax Corporation Indonesia, 2022)
The COVID-19 pandemic has impacted every aspect of people's lives as well as all industries, especially tourism. In response to the COVID-19 pandemic, which reached its peak, Indonesia imposed a ban on entry for foreign tourists. This policy is suspected to have an impact on the number of foreign tourists, micro and small companies in the provinces that have international airports as entry points for foreign tourists. The research approach applied in this scientific paper is a qualitative approach, in which researchers observe and analyze the phenomenon of changes in the number of micro, small, medium and large companies. The data collection technique applied in this scientific work is literature study. The results of this study indicate that the COVID-19 pandemic has caused a decrease in the number of foreign tourists which has led to a decrease in the number of micro-enterprises in Banten Province, Bali Province, Riau Islands Province and North Sumatra Province.